Study Of Digitalization Implementation Approach In Organizational Culture - Juanda, Enda; Santoso, Santoso; Tukiran, Martinus (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
The research has been successfully carried out. The dynamics of the international and national strategic environment have given impetus to organizational culture in exploring the digital realm through a digitalization approach. This study has the objective of describing conditions in Indonesia and several other countries in the Implementation of the Digitalization Approach in Organizational Culture. The method used in this research is a literature review approach. The data analysis carried out in this article uses a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) which is supported by references to ten articles on the same theme in this study. The results obtained are in the form of Strengths, Weaknesses, Opportunities, and Threat conditions, when implementing the digitalization approach in organizational culture it has integrative and non-integrative comparisons between the literature and theories that are currently developing. This also illustrates that the digitalization approach applied in an organizational culture both in Indonesia and in other countries has varied strengths, weaknesses, opportunities, and threats.